Metabolic Drug-Drug Interaction Potential of Macrolactin A and 7-O-Succinyl Macrolactin A Assessed by Evaluating Cytochrome P450 Inhibition and Induction and UDP-Glucuronosyltransferase Inhibition In Vitro - Bae, Soo Hyeon (American Society for Microbiology, 2014)
Macrolactin A (MA) and 7-O-succinyl macrolactin A (SMA), polyene macrolides containing a 24-membered lactone ring, show antibiotic effects superior to those of teicoplanin against vancomycin-resistant enterococci and methicillin-resistant Staphylococcus aureus. MA and SMA are currently being evaluated as antitumor agents in preclinical studies in Korea. We evaluated the potential of MA and SMA for the inhibition or induction of human liver cytochrome P450 (CYP) enzymes and UDP-glucuronosyltransferases (UGTs) in vitro to assess their safety as new molecular entities. We demonstrated that MA and SMA are potent competitive inhibitors of CYP2C9, with K(i) values of 4.06 μM and 10.6 μM, respectively. MA and SMA also weakly inhibited UGT1A1 activity, with K(i) values of 40.1 μM and 65.3 μM, respectively. However, these macrolactins showed no time-dependent inactivation of the nine CYPs studied. In addition, MA and SMA did not induce CYP1A2, CYP2B6, or CYP3A4/5. On the basis of an in vitro-in vivo extrapolation, our data strongly suggested that MA and SMA are unlikely to cause clinically significant drug-drug interactions mediated via inhibition or induction of most of the CYPs involved in drug metabolism in vivo, except for the inhibition of CYP2C9 by MA. Similarly, MA and SMA are unlikely to inhibit the activity of UGT1A1, UGT1A4, UGT1A6, UGT1A9, and UGT2B7 enzymes in vivo. Although further investigations will be required to clarify the in vivo interactions of MA with CYP2C9-targeted drugs, our findings offer a clearer understanding and prediction of drug-drug interactions for the safe use of MA and SMA in clinical practice.